In the Valley - Frederic, Harold, 1856-1898 (Salt Lake City, UT : Project Gutenberg, 2006)
"In the Valley" by Harold Frederic is a historical novel published in 1890. Set in New York's Mohawk Valley from 1757 to 1777, it follows a Dutch colonist caught between a charismatic British officer and his loyalty to the American cause. Both men vie for the same woman's affection against the backdrop of the Revolutionary War. The story builds toward the pivotal Battle of Oriskany, blending historical detail with personal drama during a time when diverse colonial communities were forging a new American identity. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/In_the_Valley
Release date is 2006-01-01
Produced by Project Gutenberg Distributed Proofreaders
Keywords: New York (State) -- History -- Fiction